On the effectiveness of loan-to-value regulation in a multiconstraint framework - Anna Grodecka (Sveriges Riksbank, 2017)
Models in the infinite horizon macro-housing literature often assume that borrowers are constrained exclusively by the loan-to-value (LTV) ratio. Motivated by the Swedish micro-data, I explore an alternative arrangement where borrowers are constrained by the feasibility of repayment, but choose a house of maximum permissible size conditional on the LTV restriction. While stricter LTV limits are often considered as a measure to tackle the rise in household indebtedness, I find that policy designed to lower the maximum permissible LTV ratio may actually leave the debt-to-GDP ratio unchanged and increase housing prices in equilibrium if borrowers are bound by two constraints at the same time. In a model with occasionally binding constraints, I show that also for the analysis of the short-run effects of different policies, the consideration of multiple constraints, possibly binding at the same time, is important. The effectiveness of LTV as a measure to tackle the rise in indebtedness has to be reassessed and is likely lower than previously shown.
Keywords: E32; E44; E58; R21; 330; borrowing constraints; household indebtedness; macroprudential policy; housing prices; loan-to-value ratio; debt-service-to-income ratio